Comparing the Ability of Secretory Signal Peptides for Heterologous Expression of Anti-Lipopolysaccharide Factor 3 in Chlamydomonas reinhardtii - Huilin Zhuang; Yaohui Ou; Ruoyu Chen; Danqiong Huang; Chaogang Wang (Marine Drugs, 2023)
Anti-lipopolysaccharide factor 3 (ALFPm3) possesses a wide antimicrobial spectrum and high antibacterial and viral activities for broad application prospects in the aquaculture industry. However, the application of ALFPm3 is limited by its low production in nature, as well as its low activity when expressed in Escherichia coli and yeast. Although it has been proven that its secretory expression can be used to produce antimicrobial peptides with strong antimicrobial activity, there is no study on the high-efficiency secretory expression of ALFPm3 in Chlamydomonas reinhardtii. In this study, signal peptides ARS1 and CAH1 were fused with ALFPm3 and inserted into the pESVH vector to construct pH-aALF and pH-cALF plasmids, respectively, that were transformed to C. reinhardtii JUV using the glass bead method. Subsequently, through antibiotic screening, DNA-PCR, and RT-PCR, transformants expressing ALFPm3 were confirmed and named T-JaA and T-JcA, respectively. The peptide ALFPm3 could be detected in algal cells and culture medium by immunoblot, meaning that ALFPm3 was successfully expressed in C. reinhardtii and secreted into the extracellular environment. Moreover, ALFPm3 extracts from the culture media of T-JaA and T-JcA showed significant inhibitory effects on the growth of V. harveyi, V. alginolyticus, V. anguillarum, and V. parahaemolyticus within 24 h. Interestingly, the inhibitory rate of c-ALFPm3 from T-JcA against four Vibrio was 2.77 to 6.23 times greater than that of a-ALFPm3 from T-JaA, indicating that the CAH1 signal peptide was more helpful in enhancing the secreted expression of the ALFPm3 peptide. Our results provided a new strategy for the secretory production of ALFPm3 with high antibacterial activity in C. reinhardtii, which could improve the application potentiality of ALFPm3 in the aquaculture industry.